2001
DOI: 10.2134/jeq2001.3041222x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Immobilization of Lead, Zinc, and Cadmium in Smelter‐Contaminated Soils Using Biosolids and Rock Phosphate

Abstract: Chemical immobilization, an in situ remediation method where inexpensive chemicals are used to reduce contaminant solubility in contaminated soil, has gained attention. We investigated the effectiveness of lime-stabilized biosolid (LSB), N-Viro Soil (NV), rock phosphate (RP), and anaerobic biosolid (AB) to reduce extractability and plant and gastrointestinal (GI) bioavailability in three Cd-, Pb-, and Zn-contaminated soils from smelter sites. Treated (100 g kg(-1) soil) and control soils were incubated at 27 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
152
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(157 citation statements)
references
References 40 publications
2
152
2
1
Order By: Relevance
“…Chemical-based S/S approach is based on the formation of thermodynamically stable and insoluble precipitate end-products with the contaminants. More effective chemical additives include phosphates and Fe-Mn oxides (Ma et al 1995, Hettiarachchi et al 2000, Basta et al 2001, Seaman et al 2001, Cao et al 2002. Phosphate has been proven to be effective in immobilizing Pb from labile soil Pb forms via formation of lead phosphate compounds such as pyromorphite-like minerals (Pb 5 (PO 4 ) 3 X, X=F, Cl, OH) by scavenging Pb from soluble Pb compounds such as cerussite (PbCO 3 ) and litharge (PbO) (Zhang & Ryan 1999, Cao et al 2002, Scheckel & Ryan 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical-based S/S approach is based on the formation of thermodynamically stable and insoluble precipitate end-products with the contaminants. More effective chemical additives include phosphates and Fe-Mn oxides (Ma et al 1995, Hettiarachchi et al 2000, Basta et al 2001, Seaman et al 2001, Cao et al 2002. Phosphate has been proven to be effective in immobilizing Pb from labile soil Pb forms via formation of lead phosphate compounds such as pyromorphite-like minerals (Pb 5 (PO 4 ) 3 X, X=F, Cl, OH) by scavenging Pb from soluble Pb compounds such as cerussite (PbCO 3 ) and litharge (PbO) (Zhang & Ryan 1999, Cao et al 2002, Scheckel & Ryan 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Significant effort has been made to evaluate the effec tiveness of phosphate on in situ remediation of contam inated waters and soils (Basta et al, 2001;Cotter-Howells and Caporn, 1996;Hettiarachchi et al, 2000;Ma et al, 1995;Yang et al, 2001). Phosphate minerals, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Basta et al [20] showed the effectiveness of lime-stabilized biosolids at reducing the extractability and bioavailability of Cd, Pb and Zn from smelter-contaminated soils, and indicated that alkaline organic treatments reduced metal extractability and phytoavailability.…”
Section: Open Accessmentioning
confidence: 99%